Sphincter of Oddi Function and Dysfunction - James Toouli; Alexander Craig (Canadian Journal of Gastroenterology)
The sphincter of Oddi (SO) is situated at the junction of the bile and pancreatic ducts where they enter the duodenum, and it serves to regulate the flow of bile and pancreatic juices as well as to prevent the reflux of duodenal contents into the pancreatobiliary system. SO dysfunction relates to either the biliary or pancreatic portions of the sphincter. Distinct clinical syndromes relating to either sphincter segment are recognized. The mechanism of dysfunction remains uncertain, but disruption of neural pathways involved in sphincter function seems likely. SO dysfunction is best diagnosed by manometry, which is able to correctly stratify patient groups and determine therapy. Biliary scintigraphy, which is noninvasive, has shown promise as a screening tool for patients with suspected SO dysfunction. Division of the sphincter is an effective treatment for patients with manometrically proven SO stenosis for either the biliary or pancreatic form of the disorder. Other forms of SO dysfunction may benefit from pharmacotherapy.